Olhares da maçonaria sobre a educação no Brasil - Egito, Philipe Henrique Teixeira do (2011)
This dissertation had as its object of study the thematic of the interfaces between Freemasonry history and its actions and precepts on education. The research began with a brief history of the Freemasonry, which revealed its first ever known educational experience: a school for girls in England. Then a profile of the Freemasonry was built mainly from the central ideas about the teaching they conducted, which gained the interest of the eighteenth century media and therefore also gained print. Another factor that contributed to constructing this profile were the propositions made by Rui Barbosa, which were weighed against the Masonic ideal in Brazil at the time. Finally, Padre Azevedo School was analysed. This school was founded in João Pessoa in 1957, marking the presence of the Freemasonry on education in the state of Paraíba. The school founded and maintained partly by the Masonry, partly by public entities and private donations was studied through thorough readings of the Masonic Lodge´s session records that enabled discussions around the school routines yielded within the Lodge to be gathered.